2022
DOI: 10.3390/math11010129
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Metaheuristics for Binary Optimization Problems: An Updated Systematic Literature Review

Abstract: For years, extensive research has been in the binarization of continuous metaheuristics for solving binary-domain combinatorial problems. This paper is a continuation of a previous review and seeks to draw a comprehensive picture of the various ways to binarize this type of metaheuristics; the study uses a standard systematic review consisting of the analysis of 512 publications from 2017 to January 2022 (5 years). The work will provide a theoretical foundation for novice researchers tackling combinatorial opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 214 publications
0
14
0
Order By: Relevance
“…The binarization techniques used in continuous MHs involve transferring continuous domain values to binary domains, with the aim of maintaining the quality of moves and generating high-quality binary solutions. While some MHs operate on binary domains without a binary scheme, studies have demonstrated that continuous MHs supported by a binary scheme perform exceptionally well on multiple NP-hard combinatorial problems [ 1 ]. Examples of such MHs include the binary bat algorithm [ 28 , 29 ], particle swarm optimization [ 30 ], binary sine cosine algorithm [ 2 , 31 , 32 , 33 ], binary salp swarm algorithm [ 34 , 35 ], binary grey wolf optimizer [ 32 , 36 , 37 ], binary dragonfly algorithm [ 38 , 39 ], the binary whale optimization algorithm [ 2 , 32 , 40 ], and the binary magnetic optimization algorithm [ 41 ].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The binarization techniques used in continuous MHs involve transferring continuous domain values to binary domains, with the aim of maintaining the quality of moves and generating high-quality binary solutions. While some MHs operate on binary domains without a binary scheme, studies have demonstrated that continuous MHs supported by a binary scheme perform exceptionally well on multiple NP-hard combinatorial problems [ 1 ]. Examples of such MHs include the binary bat algorithm [ 28 , 29 ], particle swarm optimization [ 30 ], binary sine cosine algorithm [ 2 , 31 , 32 , 33 ], binary salp swarm algorithm [ 34 , 35 ], binary grey wolf optimizer [ 32 , 36 , 37 ], binary dragonfly algorithm [ 38 , 39 ], the binary whale optimization algorithm [ 2 , 32 , 40 ], and the binary magnetic optimization algorithm [ 41 ].…”
Section: Related Workmentioning
confidence: 99%
“…In the scientific community, two-step binarization schemes are very relevant [ 1 ]. They have been widely used to solve a variety of combinatorial problems [ 47 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…algorithms [86][87][88] amongst others, [89][90][91][92][93][94][95] with many of these having been adapted for the vehicle routing problem. [96][97][98][99][100][101][102][103][104] To find solutions to the QUBO problem using traditional quantum approaches, the cost function is first mapped to an Ising Hamiltonian:…”
Section: Quadratic Unconstrained Binary Optimizationmentioning
confidence: 99%
“…The QUBO problem is a binary optimization problem consisting of finding a binary vector truex$\vec{x}^*$ such that: xbadbreak=argminx0.16emxscriptAtruex$$\begin{equation} \vec{x}^* = \underset{\vec{x}}{\textrm {arg min}}\, \vec{x}^{\top } \mathcal {A} \vec{x} \end{equation}$$where truexfalse{0,1false}nc$\vec{x}\in \lbrace 0,1\rbrace ^{n_c}$ is a vector of nc$n_c$ classical binary variables and scriptAnc×nc$\mathcal {A}^{n_c\times n_c}$ is a real and symmetric matrix constructed from our optimization problem. Classical methods of finding solutions to QUBO problems involve a range of metaheuristic algorithms such as simulated annealing, [ 76–81 ] TABU search [ 82–85 ] or genetic algorithms [ 86–88 ] amongst others, [ 89–95 ] with many of these having been adapted for the vehicle routing problem. [ 96–104 ]…”
Section: Quadratic Unconstrained Binary Optimizationmentioning
confidence: 99%